Analisis Pengaruh Religiusitas, Biaya Kepatuhan Pajak dan Penerapan E-filing Terhadap Kepatuhan Wajib Pajak (Studi Kasus Wajib Pajak Orang Pribadi Yang Terdaftar Pada KPP Pratama Demak) - Saadah, Lailatus; ., Widaryanti; Latifah, Nurul (STIE PENA, 2022)
This study aims to analyze the effect of religiosity, tax compliance costs and the application of e-filing on taxpayer compliance at KPP Pratama Demak. The population in this study is an individual taxpayer registered at the KPP Pratama Demak. Samples were taken as many as 100 respondents using the Nonprobability Sampling method, namely Accidental Sampling by taking sample members from the population based on chance and deemed suitable by the researcher. While the data collection using a questionnaire. The results of this study indicate that religiosity, tax compliance costs, and the application of e-filing have a positive effect on taxpayer compliance.Keywords: Religiosity, Tax Compliance Fee, E-filing Implementation, Taxpayer Compliance.